The Quality of Public Services: Study of Birth Certificate Making in Musi Rawas Regency, South Sumatra, Indonesia - Sari, Astriana; Alfatih, Andy; Susanto, Tri Agus (Open Access Indonesia Journal of Social Sciences, 2018)
The research, entitled Public Service Quality (Study of Making Birth Certificates for Residents in Five Districts at the Office of Population and Civil Registry of Musi Rawas Regency in 2016) is a descriptive study. with a quantitative approach. This research intends to describe and assess public perception of the quality of services provided by the Office Population and Civil Registry of Musi Rawas Regency with 94 samples. The research instrument used a questionnaire. The results using the gap analysis show that the value of the dimensions of the servqual dimension is negative (< 0), this value indicates that the quality of making birth certificate services for residents in five districts in the Population and Civil Registry Office of Musi Rawas Regency is not good. Factors affecting the quality of making birth certificate services for residents in five districts in the Population and Civil Registry Office of Musi Rawas Regency are a neat and clean in service room, complete service facilities available, the ability of officers to answer community questions, officers provide information to community, window attendants provide services to all communities regardless of social status. Based on these results it can be suggested that the five dimensions which are in the high and good value category need to be maintained, while those in the medium or near the low and valuable categories good enough needs to be improved again, and still needs to be done a little change by completing the existing deficiencies and providing better supporting facilities so that people can come to visit to make Birth Certificates.